Extraskeletal Osteosarcomas: A Case Made for Combined Modality Local Therapy With Radiation and Surgery. (March 2019) - Bishop, Andrew J.; Livingston, J. Andrew; Araujo, Dejka M.; Moon, Bryan S.; Patel, Shreyaskumar; Wang, Wei-Lien; Lazar, Alexander J.; Roland, Christina L.; Guadagnolo, B. Ashleigh
Abstract : Objective: We evaluated our experience treating patients with extraskeletal osteosarcoma (ESOS) using combined modality local therapy, including surgery and radiation therapy (RT), to investigate local control (LC) and other survival endpoints. Methods: We reviewed the records of 21 consecutive patients with nonmetastatic, ESOS treated with RT in combination with surgery at our institution from 1984 to 2015. Postoperative RT was used for 10 patients (48%) to a median dose of 60 Gy (range, 60 to 68 Gy). The other 11 patients (52%) received 50 Gy preoperatively. Seven patients (33%) were treated with neoadjuvant or adjuvant chemotherapy. Among the patients who received chemotherapy, all were treated with doxorubicin and ifosfamide for a median of 6 cycles (range, 4 to 6). Results: Median follow-up time was 120 months (range, 6 to 200 mo). Larger tumor size (>5 cm) was associated with chemotherapy use ( P =0.046). The 5-year LC, distant metastatic free survival, and disease-specific survival rates were 93%, 53%, and 62%, respectively. Only 1 patient (5%) had a local recurrence at 22 months. Nine patients (43%) developed distant metastases at a median time of 9 months (range, 1 to 30 mo) without any significant factors for reduced distant metastatic free survival. Following disease relapse, there were 2 patients who were ultimately salvaged, both of whom were treated with chemotherapy and surgery. Conclusions: RT in combination with surgery provides favorable LC for patients with ESOS. However, patients have a high rate of distant metastases with limited salvage.